PHYTOCHEMICAL PROFILING OF CRUDE EXTRACTS FROM RADERMACHERA XYLOCARPA (ROXB.) K. SCHUM. - DINESH D. KHEDKAR; ANAND V. OKE (International Journal of Pharma and Bio Sciences, 2013)
Extinction is a natural phenomenon which costs loss of around nine percent of the species every million years . Medicinally important plants are facing threat of extinction due to various reasons like habitat destruction, illegal trade and over exploitation in addition to climate change. These plants may vanish without complete knowledge of its biochemical attributes which endow them potential to cure numerous diseases. This has urged to study the complete phytochemical profile of such RET species to explore its appropriate medicinal value and the biomolecules behind those properties. Qualitative phytochemical investigation of plant parts like bark, wood, leaves and pods of Radermachera xylocarpa (ROXB.) K. SCHUM. was carried out with five different solvent extracts. Overall analysis revealed absence of tannins in almost all plant parts with the exception of water and ethanol extracts from the leaf. The alkaloids, steroids, terpenoids, cardiac glycosides, flavonoids, triterpenoids, etc. were reported in various plant parts in different extraction systems.